Regulation of Autophagy by Sphingolipids - Bedia, Carmen; Levade, Thierry; Codogno, Patrice (Anti-Cancer Agents in Medicinal Chemistry, 2011)
Autophagy is an evolutionary conserved process by which cells recycle intracellular materials to maintain homeostasis in different cellular contexts. Under basal conditions it prevents accumulation of damaged proteins and organelles; during starvation, autophagy provides cells with sufficient nutrients to survive. Sphingolipids are a family of bioactive molecules modulating vital cellular functions such as apoptosis, cell cycle arrest or proliferation. Besides these functions, some sphingolipids like ceramide, sphingosine- 1-phosphate or gangliosides have been described to promote autophagy in several cancer cell lines. Current evidence supports the notion that induction of autophagic cell death can halt tumorigenesis. Of interest, some chemotherapeutic agents used for the treatment of hematological malignancies trigger the production of endogenous sphingolipids with pro-autophagic effects. In this review we describe the regulation and functions of the sphingolipid-induced autophagy and the tight relationship with the cancer cell response to current chemotherapeutic regimens.
Keywords: JNK